Ultrasound-triggered with ROS-responsive SN38 nanoparticle for enhanced combination cancer immunotherapy - Liu, Hongyu; Shi, Yunpeng; Ji, Guofeng; Wang, Jukun; Gai, Baodong (Frontiers in Immunology, 2024)
Controlled generation of cytotoxic reactive oxygen species (ROS) is essential in cancer therapy. Ultrasound (US)-triggered sonodynamic therapy (SDT) has shown considerable ability to trigger in situ ROS generation. Unfortunately, US therapy alone is insufficient to trigger an efficient anticancer response, owing to the induction of multiple immunosuppressive factors. It was identified that 7-ethyl-10-hydroxycamptothecin (SN38) could notably inhibit DNA topoisomerase I, induce DNA damage and boost robust anticancer immunity. However, limited by the low metabolic stability, poor bioavailability, and dose-limiting toxicity, the direct usage of SN38 is inadequate in immune motivation, which limits its clinical application. Hence, new strategies are needed to improve drug delivery efficiency to enhance DNA topoisomerase I inhibition and DNA damage and elicit a vigorous anticancer cancer immunity response. Considering US irradiation can efficiently generate large amounts of ROS under low-intensity irradiation, in this study, we aimed to design a polymeric, ROS-responsive SN38 nanoformulation for in vivo drug delivery. Upon the in-situ generation of ROS by US therapy, controlled on-demand release of SN38 occurred in tumor sites, which enhanced DNA damage, induced DC cell maturation, and boosted anticancer immunity. Our results demonstrated that a new strategy of involving the combination of a SN38 nanoformulation and US therapy could be used for cancer immunotherapy.